PELAKSANAAN KOORDINASI DALAM MITIGASI BENCANA DI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN SUMEDANG - Cahyadi (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to analyze the implementation of disaster mitigation at the Sumedang Regency Regional Disaster Management Agency (BPBD), as well as identifying inhibiting factors and efforts made in disaster management. The research method used is descriptive qualitative with a case study approach. The research results show that the implementation of disaster mitigation at the Sumedang BPBD has gone well, especially in terms of communication, coordination, human resource competency, and outreach through the Disaster Resilient Village (DESTANA) program. However, there are obstacles in the performance of the Rapid Response Team caused by organizational conditions and limited human resources. Efforts to overcome these obstacles include increasing communication, synchronizing between implementers, and optimizing existing resources. Researchers recommend that BPBD make more efforts to develop disaster risk management programs, add supporting facilities, and regularize training to improve the quality of human resources. In this way, it is hoped that disaster management in Sumedang Regency can run more effectively and efficiently.